Cognitive Poetics: The scope of problems and vectors of research - Vorobyova, O. (Studia Philologica, 2021)
This lecture delineates the problem field of Cognitive Poetics from historical and typological, theoretical and methodological as well as research perspectives with a special emphasis upon the sources of Cognitive Poetics studies of literary text, viewed in terms of paradigm shifts and through the lens of various research schools and personalities. It suggests a modified version of the poetics’ mereological model, while highlighting their typology with regard to the ways of literary reference and world representation in literary text. The lecture reveals the research motifs of philologists who address the realm of literary text cognitive studies. The paper also defines the basic principles of the Cognitive Poetics approach to literary text. It surveys the state of the art within the realm of Cognitive Poetics in Ukraine and beyond, taking into account its various research trends and varieties. The lecture concludes with an overview of current issues taken up by Ukrainian linguopoetologists who work in the area of literary text cognitive studies.